Oxidation catalyst, preparation method and application thereof, and propylene selective oxidation method

The Bi/(MoFeXcYdZe)Oj catalyst composition with sol-gel processing and acid loading addresses the low stability and yield issues in propylene oxidation by ensuring Bi-O active site exposure, enhancing catalytic performance and propylene oxide and acid production.

CN119701987AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202311273203.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Existing oxidation catalysts have low structural stability and low yield rates for target products in olefin oxidation processes, particularly in the selective oxidation of propylene to propylene oxide, where the catalyst's activity and selectivity are compromised by thermal hotspots and limited Bi dispersion.

Method used

A catalyst composition of Bi/(MoFeXcYdZe)Oj, where X includes Mg, Co, Ni, Ca, Cu, Zn, Mn, Y includes La, Ce, and Z includes K, Rb, Na, Cs, with Bi surface dispersion of 1-3, is used, and a method involving sol-gel processing and acid loading to enhance Bi exposure and activity, improving catalyst stability and propylene oxide yield.

Benefits of technology

The catalyst exhibits enhanced propylene oxide and acid total collection rates under high load conditions, maintaining stability and improving catalytic performance by ensuring Bi-O active sites are exposed, thus increasing propylene oxide and acid production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701987A_ABST
    Figure CN119701987A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to an oxidation catalyst, a preparation method and application thereof and a propylene selective oxidation method, the general formula of the catalyst is Bia / (MoFebXcYdZe) Oj, and X is selected from at least one of Mg, Co, Ni, Ca, Cu, Zn and Mn; y is selected from at least one of La and Ce; z is selected from at least one catalyst of K, Rb, Na and Cs, and the surface dispersity of the # imgabs0 # Bi element is 1-3. The catalyst is used for oxidation reactions such as propylene selective oxidation for preparation of acrolein and / or acrylic acid, has the advantage of high total yield of acrolein and acrylic acid, and has good structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to an oxidation catalyst and a preparation method and application thereof, and a propylene selective oxidation method. Background Art

[0002] The selective oxidation of olefins to prepare unsaturated acids is an important chemical process. In industry, olefins are usually oxidized to obtain unsaturated aldehydes, and then the unsaturated aldehydes are oxidized to obtain unsaturated acids. This process usually adopts two-stage production, using two reactors and two catalysts under different reaction conditions. One stage of reaction mainly produces acrolein, and about 20% of acrylic acid. The active components of the catalyst are complex Mo and Bi composite oxide systems. The improvement of the catalyst is mainly carried out from the aspects of catalyst activity and stability, such as adding transition metals to the active components to improve activity and increase the single yield of the product; adding rare earth elements to improve redox ability; adding Fe, Co, Ni and other elements to inhibit the sublimation of Mo, stabilize the active components of the catalyst, and increase the service life of the catalyst. In addition, due to the violent exothermic phenomenon in the reaction, it is very important to control the reaction temperature of the catalyst bed. The formation of hot spots not only deteriorates the reaction results, but also shortens the service life of the catalyst and affects the stable operation of the device.

[0003] It is generally believed that in the first step of the propylene oxidation reaction to produce acrolein, the olefin is adsorbed on the catalyst surface, an α-H is removed by the metal oxide, and a free radical intermediate is formed, which is then inserted into the active nitrogen to generate the product. In this process, the catalyst will undergo a redox cycle, in which it loses the oxygen atom involved in the insertion reaction, is reduced, and then is reoxidized by the oxygen in the reaction gas, and the active oxygen atom is supplemented by oxygen migration. Therefore, the catalyst is required to have good oxygen migration energy in order to maintain the catalyst structure and redox balance. Generally, transition metal composite oxides such as Mo, V, Bi, Te, Nb, and Fe are used (Catalysis Today 49 (1999) 141-153)

[0004] US4224187 and US4248803 proposed to improve the olefin conversion rate and target product yield by improving the catalyst composition and their usage ratio and catalyst preparation method. For the selective oxidation of isobutylene, there is a problem of low reaction selectivity. The isobutylene conversion rate is as high as 99%, but the total yield of methacrolein and methacrylic acid is only 73.6%.

[0005] US6268529 proposes a propylene oxidation catalyst with a propylene conversion rate of 98.1%, an acrolein yield of 65.3%, an acrylic acid yield of 20.8%, and a total yield of acrolein and acrylic acid of 86.1%.

[0006] CN1564709 improves catalyst performance by adding organic carboxylic acid to overcome the catalyst unevenness caused by the stratification of metal salts during the catalyst preparation coprecipitation process. It is used for the selective oxidation reaction of propylene, wherein the propylene conversion rate is as high as 98.12%, the acrolein selectivity is as high as 82.53%, and the total yield of acrolein and acrylic acid is 91.05%.

[0007] CN1210511A, CN1283604A and CN1314331A achieve the purpose of controlling the reaction hot spots and prolonging the catalyst stability by configuring multiple catalyst layers with gradually increasing reaction activity along the axial direction of the reactor from the reaction gas inlet to the outlet. However, the structural stability of the catalyst needs to be further improved. Summary of the invention

[0008] The purpose of the present invention is to overcome the problems of low structural stability of oxidation catalysts in the prior art and low yield of target products for oxidation catalysis, and to provide an oxidation catalyst and a preparation method and application thereof and a propylene selective oxidation method. The catalyst is used for oxidation reactions such as selective oxidation of propylene to prepare acrolein and / or acrylic acid, and has the advantages of high total yield of acrolein and acrylic acid, and good catalyst structural stability.

[0009] In order to achieve the above object, the present invention provides an oxidation catalyst, the general formula of the catalyst is: Bi a / (MoFe b X c Y d Z e ) j , wherein X is selected from at least one of Mg, Co, Ni, Ca, Cu, Zn, and Mn; Y is selected from at least one of La and Ce; Z is selected from at least one of K, Rb, Na, and Cs; a is the molar ratio of Bi to Mo, and the value of a is 0.1 to 0.3; b is the molar ratio of Fe to Mo, and the value of b is 0.1 to 0.5; c is the molar ratio of X to Mo, and the value of c is 0.5 to 1.5; d is the molar ratio of Y to Mo, and the value of d is 0.1 to 0.5; e is the molar ratio of Z to Mo, and the value of e is 0.01 to 0.06; j is the total number of oxygen atoms required to satisfy the valence of other elements; in the catalyst,

[0010] The surface dispersion of Bi element is 1-3.

[0011]

[0012] A second aspect of the present invention provides a method for preparing an oxidation catalyst, the method comprising:

[0013] (1) dissolving a Mo compound and a Z compound in water to form a first solution; dissolving an Fe compound, an X compound and a Y compound in water to obtain a second solution; mixing the first solution and the second solution to obtain a slurry, and concentrating, drying and calcining to obtain a solid precursor;

[0014] (2) crushing the solid precursor, molding it with a binder and water, drying it, and calcining it to obtain a molded precursor;

[0015] (3) Dissolving the Bi compound in an acid solution to obtain a third solution, impregnating the third solution onto the molded precursor, and drying and calcining to obtain a catalyst.

[0016] The third aspect of the present invention provides an oxidation catalyst prepared by the preparation method described in the present invention.

[0017] A fourth aspect of the present invention provides an application of the oxidation catalyst of the present invention or the oxidation catalyst prepared by the preparation method in the oxidation of olefins to prepare olefinic aldehydes and / or olefinic acids.

[0018] A fifth aspect of the present invention provides a method for selective oxidation of propylene, the method comprising: contacting a raw gas containing propylene and an oxidizing gas containing oxygen with a catalyst to prepare acrolein and / or acrylic acid; the catalyst comprises the oxidation catalyst described in the present invention or the oxidation catalyst prepared by the preparation method described in the present invention.

[0019] Through the above technical scheme, in the oxidation catalyst described in the present invention, the active component Bi is distributed in the catalyst, Bi has good dispersion on the catalyst surface, can form abundant surface active sites, and improve the oxidation activity of the catalyst and the product yield.

[0020] Mo-Bi system composite oxide is an important catalytic system for selective oxidation or ammoxidation of olefins, and Bi is considered to be the key active site for the first step of dehydrogenation. The catalyst of the present invention can better disperse and expose the Bi component on the surface accessible to the reaction gas, providing more Bi-O active sites. Therefore, the catalytic performance of the catalyst can be well improved, especially the catalytic performance under high load conditions.

[0021] The catalyst of the present invention is used for the reaction of olefin (such as propylene) oxidation to prepare olefin aldehyde (such as acrolein) and olefin acid (such as acrylic acid), and has the advantage of high total yield of olefin aldehyde and olefin acid, especially under high load conditions.

[0022] The preparation method of the oxidation catalyst of the present invention adopts the method of first molding and then loading Bi in the acidic solution, which can avoid Bi precipitation and being covered by other components, and can also avoid the Bi component being covered during the secondary molding process. It can better disperse and expose the Bi component on the surface accessible to the reaction gas, providing more Bi-O active sites. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] In the present invention, in the reaction of olefin (such as propylene) oxidation to prepare olefin aldehyde (such as acrolein) and olefin acid (such as acrylic acid), the high load condition refers to the raw gas volume mass space velocity of 1500-3000 mL / g·h.

[0025] In one aspect, the present invention provides an oxidation catalyst, the general formula of the catalyst is: Bi a / (MoFe b X c Y d Z e ) j , wherein X is selected from at least one of Mg, Co, Ni, Ca, Cu, Zn, and Mn; Y is selected from at least one of La and Ce; Z is selected from at least one of K, Rb, Na, and Cs; a is the molar ratio of Bi to Mo, and the value of a is 0.1 to 0.3; b is the molar ratio of Fe to Mo, and the value of b is 0.1 to 0.5; c is the molar ratio of X to Mo, and the value of c is 0.5 to 1.5; d is the molar ratio of Y to Mo, and the value of d is 0.1 to 0.5; e is the molar ratio of Z to Mo, and the value of e is 0.01 to 0.06; j is the total number of oxygen atoms required to satisfy the valence of other elements; in the catalyst,

[0026]

[0027] The surface dispersion of Bi element is 1-3.

[0028] In the oxidation catalyst of the present invention, by changing the distribution of the key active component Bi in the catalyst, Bi has good dispersion on the catalyst surface, can form abundant surface active sites, and improve the oxidation activity of the catalyst and the product yield.

[0029] In the present invention, the Bi content on the catalyst surface and the content of all metals on the catalyst surface are measured by XPS. The Bi content in the catalyst and the content of all metals in the catalyst are measured by ICP.

[0030] According to a preferred embodiment of the present invention, the surface dispersion of Bi element is 1.2-2.8.

[0031] According to a preferred embodiment of the present invention, the value of a is 0.15-0.2, which is beneficial to improving the oxidation activity of the catalyst and the product yield.

[0032] According to a preferred embodiment of the present invention, the value of b is 0.15 to 0.3, which is beneficial to improving the oxidation activity of the catalyst and the product yield.

[0033] According to a preferred embodiment of the present invention, the value of c is 0.7-1.2, which is beneficial to improving the oxidation activity of the catalyst and the product yield.

[0034] According to a preferred embodiment of the present invention, the value of d is 0.15 to 0.3, which is beneficial to improving the oxidation activity of the catalyst and the product yield.

[0035] According to a preferred embodiment of the present invention, the value of e is 0.02 to 0.05, which is beneficial to improving the oxidation activity of the catalyst and the product yield.

[0036] According to a preferred embodiment of the present invention, X is selected from Co and Ni, and preferably, the molar ratio of Co to Ni is 0.5-2; the oxidation catalyst of the present invention contains both Co and Ni, which has a synergistic effect and can improve the oxidation activity of the catalyst and the product yield.

[0037] According to a preferred embodiment of the present invention, Y is selected from La and Ce, and preferably, the molar ratio of La to Ce is 0.5-2; the oxidation catalyst of the present invention contains La and Ce at the same time, which has a synergistic effect and can improve the oxidation activity of the catalyst and the product yield.

[0038] A second aspect of the present invention provides a method for preparing an oxidation catalyst, the method comprising:

[0039] (1) dissolving a Mo compound and a Z compound in water to form a first solution; dissolving an Fe compound, an X compound and a Y compound in water to obtain a second solution; mixing the first solution and the second solution to obtain a slurry, and concentrating, drying and calcining to obtain a solid precursor;

[0040] (2) crushing the solid precursor, molding it with a binder and water, drying it, and calcining it to obtain a molded precursor;

[0041] (3) Dissolving the Bi compound in an acid solution to obtain a third solution, impregnating the third solution onto the molded precursor, drying, and calcining to obtain the catalyst. The method of molding first and then loading Bi in the acid solution can avoid Bi precipitation and being covered by other components, and can also avoid the Bi component being covered during the secondary molding process, and can better disperse and expose the Bi component on the surface accessible to the reaction gas, providing more Bi-O active sites.

[0042] In the present invention, the amount of each substance fed to the catalyst is such that the general formula of the catalyst prepared is: Bi a / (MoFe b X c Y d Z e ) j , wherein X is selected from at least one of Mg, Co, Ni, Ca, Cu, Zn, and Mn; Y is selected from at least one of La and Ce; Z is selected from at least one of K, Rb, Na, and Cs; a is the molar ratio of Bi to Mo, and the value of a is 0.1 to 0.3; b is the molar ratio of Fe to Mo, and the value of b is 0.1 to 0.5; c is the molar ratio of X to Mo, and the value of c is 0.5 to 1.5; d is the molar ratio of Y to Mo, and the value of d is 0.1 to 0.5; e is the molar ratio of Z to Mo, and the value of e is 0.01 to 0.06; j is the total number of oxygen atoms required to satisfy the valence of other elements.

[0043] According to a preferred embodiment of the present invention, the Mo compound, the Y compound, the Bi compound, the Fe compound, the X compound and the Z compound can be selected from nitrates, ammonium salts, sulfates, oxides, hydroxides, chlorides, acetates and the like.

[0044] According to a preferred embodiment of the present invention, the Mo compound may be selected from but not limited to: one or more of ammonium molybdate, molybdenum trioxide, molybdenum nitrate, molybdic acid and sodium molybdate.

[0045] According to a preferred embodiment of the present invention, the Bi compound may be selected from but not limited to: one or more of bismuth nitrate, bismuth trioxide, bismuth sulfate, bismuth chloride and bismuth acetate.

[0046] According to a preferred embodiment of the present invention, the Fe compound may be selected from but not limited to: one or more of ferric nitrate, ferric sulfate, ferric chloride, ferric oxide and ferrous sulfate.

[0047] According to a preferred embodiment of the present invention, the X compound can be selected from but not limited to: one or more of cobalt nitrate, cobalt sulfate, cobalt chloride, magnesium nitrate, magnesium sulfate, magnesium chloride, magnesium oxide, magnesium acetate, nickel nitrate, nickel sulfate, nickel chloride, calcium nitrate, calcium acetate, calcium chloride, copper nitrate, zinc nitrate and manganese nitrate.

[0048] According to a preferred embodiment of the present invention, the Y compound can be selected from but not limited to: one or more of lanthanum nitrate, cerium nitrate, cerium sulfate, cerium perchlorate, cerium dioxide and cerium acetate.

[0049] According to a preferred embodiment of the present invention, the Z compound can be selected from but not limited to: one or more of potassium nitrate, rubidium nitrate, sodium nitrate, sodium sulfate, sodium chloride, sodium acetate, sodium hydroxide and cesium nitrate.

[0050] According to a preferred embodiment of the present invention, the amount of water in the first solution and the second solution and the amount of nitric acid solution in the third solution have a wide selection range, in order to fully dissolve the compound.

[0051] According to a preferred embodiment of the present invention, in step (2), the solid precursor is crushed into particles smaller than 100 microns.

[0052] In the present invention, in step (2), the drying conditions have a wide range of optional ranges. According to a preferred embodiment of the present invention, the drying conditions include: a temperature of 100-150°C; and a drying time that can be reasonably determined according to actual needs, preferably, the time is 1-4h.

[0053] In the present invention, in step (2), the range of roasting conditions is relatively wide. According to a preferred embodiment of the present invention, the roasting conditions include: a temperature of 350-450°C; and a roasting time that can be reasonably determined according to actual needs, preferably, the time is 1-3h.

[0054] In the present invention, in step (2), the type of the binder can be selected from a wide range, as long as it can bond the wet material into shape. According to a preferred embodiment of the present invention, the binder is selected from at least one of methyl cellulose, hydroxypropyl methyl cellulose and carboxymethyl cellulose.

[0055] In the present invention, in step (2), there is no particular limitation on the shape of the molded precursor, as long as it is suitable for loading into the reactor. For example, the molded precursor can be prepared into Raschig rings, spheres, gears, honeycombs, etc.

[0056] According to a preferred embodiment of the present invention, in step (3), the mass concentration of the acid in the acid-containing solution is 3wt-20wt%; preferably, the acid is selected from nitric acid.

[0057] According to a preferred embodiment of the present invention, in step (3), the impregnation method is equal volume impregnation.

[0058] In the present invention, in step (3), the drying conditions have a wide range of optional ranges. According to a preferred embodiment of the present invention, the drying conditions include: a temperature of 80-100°C; and a drying time that can be reasonably determined according to actual needs, preferably, the time is 2-10h.

[0059] In the present invention, in step (3), the range of roasting conditions is relatively wide. According to a preferred embodiment of the present invention, the roasting conditions include: a temperature of 500-600°C; and a roasting time that can be reasonably determined according to actual needs, preferably, the time is 1-6h.

[0060] According to a preferred embodiment of the present invention, in step (2) and step (3), the calcination atmosphere is respectively an atmosphere containing O2. However, from an economic point of view, the calcination atmosphere is preferably air. Unless otherwise specified, the calcination atmosphere in the present invention is air.

[0061] According to a preferred embodiment of the present invention, the solution after mixing in each process is a homogeneous solution, a suspension or a mixture of a solution and a suspension.

[0062] In the present invention, a solid can be obtained by steps such as concentration. For the present invention, the solid is preferably obtained by evaporation concentration at 60 to 80°C.

[0063] The third aspect of the present invention provides an application of the oxidation catalyst of the present invention or the oxidation catalyst prepared by the preparation method in the oxidation of olefins to prepare olefins and / or olefinic acids. The catalyst of the present invention is used for the oxidation of olefins (such as propylene) to prepare olefins (such as acrolein) and olefinic acids (such as acrylic acid), and has the advantage of high total yield of olefins and olefinic acids, especially high total yield of olefins and olefinic acids under high load conditions.

[0064] A fourth aspect of the present invention provides a method for selective oxidation of propylene, the method comprising: contacting a raw gas containing propylene and an oxidizing gas containing oxygen with a catalyst to prepare acrolein and / or acrylic acid; the catalyst comprises the oxidation catalyst described in the present invention or the oxidation catalyst prepared by the preparation method described in the present invention.

[0065] According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 300-550°C, preferably 330-380°C.

[0066] According to a preferred embodiment of the present invention, the contact conditions include: a pressure of 0.01 to 0.08 MPa, wherein the pressure is a gauge pressure.

[0067] According to a preferred embodiment of the present invention, the contact conditions include: the raw gas volume mass space velocity is 1500-3000 mL / g·h.

[0068] According to a preferred embodiment of the present invention, the contact conditions include: in volume ratio, propylene: oxygen-containing oxidizing gas = 1: (6-8).

[0069] According to a preferred embodiment of the present invention, in order to make the reaction more stable and controllable, the raw gas further contains a diluent gas phase material; in terms of volume ratio, propylene: diluent gas phase material = 1: (0.5-5).

[0070] According to a preferred embodiment of the present invention, the diluent gas phase material is water vapor.

[0071] According to a preferred embodiment of the present invention, the oxygen-containing oxidizing gas may be pure oxygen or oxygen-enriched gas, but air is preferred from an economical point of view.

[0072] In the following examples and comparative examples, the catalyst evaluation conditions are as follows:

[0073] Reactor: Fixed bed single tube reactor, inner diameter 26.0 mm, reactor length 800 mm

[0074] Catalyst: 200 g

[0075] Reaction temperature: 360℃

[0076] Reaction pressure: 0.05MPa (gauge pressure)

[0077] Propylene: air (raw material molar ratio) = 1: 7.2

[0078] Propylene: water vapor = 1: 1.8

[0079] Raw gas volume mass space velocity: 2000mL / g·h

[0080] The reaction product was absorbed by 0°C dilute acid and analyzed by gas chromatography (Agilent 7890A). The carbon balance was calculated and the data were valid when the carbon balance was (95-105)%.

[0081] Propylene conversion, product yield and selectivity are defined as:

[0082]

[0083]

[0084]

[0085] Example 1

[0086] (1) Weigh 1 mol of Mo ammonium heptamolybdate and 0.04 mol of K potassium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.2 mol of Fe ferric nitrate, 0.7 mol of Co cobalt nitrate, 0.2 mol of Ni nickel nitrate and 0.2 mol of Ce cerium nitrate and dissolve them in 200 ml of water to form a second solution. The first solution and the second solution are mixed to obtain a slurry, which is concentrated at 70° C., dried at 100° C. for 12 h, and then calcined at 300° C. for 2 h to obtain a solid precursor.

[0087] (2) The solid precursor was crushed, sieved through 200 mesh, and water and methyl cellulose were added to extrude and cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm. The rings were dried at 120° C. for 3 h, and calcined at 400° C. for 2 h to obtain a molded precursor.

[0088] (3) Weigh 0.2 mol of bismuth nitrate and dissolve it in 50 g of 10 wt% nitric acid solution to obtain a third solution. Impregnate an equal volume of the third solution onto the molded precursor, bake at 90° C. for 6 h, and calcine at 550° C. for 4 h to obtain a catalyst Bi. 0.2 / (MoFe 0.2 Co 0.7 Ni 0.2 Ce 0.2 K 0.04 ) j .

[0089] Example 2

[0090] (1) Weigh 1 mol of Mo in mol ammonium heptamolybdate and 0.01 mol of Cs in cesium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.1 mol of Fe in ferric nitrate, 1.5 mol of Co in cobalt nitrate, 0.2 mol of Ce in cerium nitrate and 0.3 mol of La in lanthanum nitrate and dissolve them in 200 ml of water to form a second solution, mix the first solution and the second solution to obtain a slurry, concentrate at 70°C, dry at 100°C for 12 h, and calcine at 300°C for 2 h to obtain a solid precursor.

[0091] (2) The solid precursor was crushed, sieved through a 200-mesh sieve, and water and methyl cellulose were added to extrude and cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm. The rings were dried at 120° C. for 3 h, and calcined at 400° C. for 2 h to obtain a molded precursor.

[0092] (3) Weigh 0.1 mol of bismuth nitrate and dissolve it in 50 g of 10% nitric acid solution to obtain a third solution. The third solution is impregnated onto the molded precursor, and then baked at 90° C. for 6 h and calcined at 550° C. for 4 h to obtain the catalyst Bi. 0.1 / (MoFe 0.1 Co 1.5 Ce0.2 La 0.3 Cs 0.01 ) j .

[0093] Example 3

[0094] (1) Weigh 1 mol of Mo ammonium heptamolybdate, 0.04 mol of K potassium hydroxide and 0.01 mol of Na sodium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.5 mol of Fe iron nitrate, 0.5 mol of Cu copper nitrate and 0.1 mol of Ce cerium nitrate and dissolve them in 200 ml of water to form a second solution, mix the first solution and the second solution to obtain a slurry, concentrate at 70°C, dry at 100°C for 12 h, and calcine at 300°C for 2 h to obtain a solid precursor.

[0095] (2) The solid precursor was crushed, sieved through a 200-mesh sieve, and an appropriate amount of water and methyl cellulose were added to extrudates and cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm. The rings were dried at 120° C. for 3 h, and calcined at 400° C. for 2 h to obtain a molded precursor.

[0096] (3) Weigh 0.3 mol of bismuth nitrate and dissolve it in 50 g of 10% nitric acid solution to obtain a third solution. The third solution is impregnated onto the molded precursor, and then baked at 90° C. for 6 h and calcined at 550° C. for 4 h to obtain a catalyst Bi. 0.3 / (MoFe 0.5 Cu 0.5 Ce 0.1 K 0.04 Na 0.01 ) j .

[0097] Example 4

[0098] (1) Weigh 1 mol of Mo ammonium heptamolybdate and 0.04 mol of K potassium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.2 mol of Fe ferric nitrate, 0.9 mol of Co cobalt nitrate and 0.2 mol of Ce cerium nitrate and dissolve them in 200 ml of water to form a second solution. Mix the first solution and the second solution to obtain a slurry, concentrate at 70° C., dry at 100° C. for 12 h, and calcine at 300° C. for 2 h to obtain a solid precursor.

[0099] (2) The solid precursor was crushed, sieved through 200 mesh, and water and methyl cellulose were added to extrude and cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm. The rings were dried at 120° C. for 3 h, and calcined at 400° C. for 2 h to obtain a molded precursor.

[0100] (3) Weigh 0.2 mol of bismuth nitrate and dissolve it in 50 g of 10 wt% nitric acid solution to obtain a third solution. Impregnate an equal volume of the third solution onto the molded precursor, bake at 90° C. for 6 h, and calcine at 550° C. for 4 h to obtain a catalyst Bi. 0.2 / (MoFe 0.2 Co 0.9 Ce 0.2 K 0.04 ) j .

[0101] The method of Example 1 is followed, except that in step (1), cobalt nitrate equivalent to 0.2 mol of Co is used instead of nickel nitrate equivalent to 0.2 mol of Ni, and the remaining conditions are the same as those of Example 1.

[0102] Example 5

[0103] (1) Weigh 1 mol of Mo ammonium heptamolybdate and 0.04 mol of K potassium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.2 mol of Fe ferric nitrate, 0.7 mol of Co cobalt nitrate, 0.2 mol of Ni nickel nitrate, 0.1 mol of La lanthanum nitrate and 0.1 mol of Ce cerium nitrate and dissolve them in 200 ml of water to form a second solution, mix the first solution and the second solution to obtain a slurry, concentrate at 70°C, dry at 100°C for 12 h, and calcine at 300°C for 2 h to obtain a solid precursor.

[0104] (2) The solid precursor was crushed, sieved through 200 mesh, and water and methyl cellulose were added to extrude and cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm. The rings were dried at 120° C. for 3 h, and calcined at 400° C. for 2 h to obtain a molded precursor.

[0105] (3) Weigh 0.2 mol of bismuth nitrate and dissolve it in 50 g of 10 wt% nitric acid solution to obtain a third solution. Impregnate an equal volume of the third solution onto the molded precursor, bake at 90° C. for 6 h, and calcine at 550° C. for 4 h to obtain a catalyst Bi. 0.2 / (MoFe 0.2 Co 0.7 Ni 0.2 La 0.1 Ce 0.1 K 0.04 ) j .

[0106] The method of Example 1 is followed, except that in step (1), lanthanum nitrate equivalent to 0.1 mol of La is used instead of cerium nitrate equivalent to 0.1 mol of Ce, and the remaining conditions are the same as those of Example 1.

[0107] Example 6

[0108] (1) Weighing ammonium heptamolybdate equivalent to 1 mol of Mo and potassium hydroxide 0.04 mol of K and dissolving them in 200 ml of water to form a first solution; weighing ferric nitrate equivalent to 0.2 mol of Fe, cobalt nitrate 0.7 mol of Co, nickel nitrate 0.2 mol of Ni and lanthanum nitrate 0.2 mol of lanthanum and dissolving them in 200 ml of water to form a second solution, mixing the first solution and the second solution to obtain a slurry, concentrating at 70° C., drying at 100° C. for 12 h, and calcining at 300° C. for 2 h to obtain a solid precursor.

[0109] (2) The solid precursor was crushed, sieved through 200 mesh, and water and methyl cellulose were added to extrude and cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm. The rings were dried at 120° C. for 3 h, and calcined at 400° C. for 2 h to obtain a molded precursor.

[0110] (3) Weigh 0.2 mol of bismuth nitrate and dissolve it in 50 g of 10 wt% nitric acid solution to obtain a third solution. Impregnate an equal volume of the third solution onto the molded precursor, bake at 90° C. for 6 h, and calcine at 550° C. for 4 h to obtain a catalyst Bi. 0.2 / (MoFe 0.2 Co 0.7 Ni 0.2 La 0.2 K 0.04 ) j .

[0111] The method of Example 1 is followed, except that in step (1), lanthanum nitrate equivalent to 0.2 mole of La is used instead of cerium nitrate equivalent to 0.2 mole of Ce, and the remaining conditions are the same as those of Example 1.

[0112] Comparative Example 1

[0113] (1) Weigh 1 mol of Mo ammonium heptamolybdate and 0.04 mol of K potassium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.2 mol of Fe ferric nitrate, 0.2 mol of Bi bismuth nitrate, 0.7 mol of Co cobalt nitrate, 0.2 mol of Ni nickel nitrate and 0.2 mol of Ce cerium nitrate and dissolve them in 200 ml of water to form a second solution, mix the first solution and the second solution to obtain a slurry, concentrate at 70°C, dry at 100°C for 12 h, and calcine at 300°C for 2 h to obtain a solid precursor.

[0114] (2) The solid precursor was crushed, sieved through 200 mesh, added with appropriate amount of water and methyl cellulose, extruded and cut into Raschig rings with outer diameter of 5 mm, inner diameter of 3.5 mm and length of 4.5 mm, dried at 120°C for 3 h, and calcined at 400°C for 2 h to obtain a shaped precursor. The catalyst Bi was obtained by drying at 90°C for 6 h and calcining at 550°C for 4 h. 0.2 MoFe0.2 Co 0.7 Ni 0.2 Ce 0.2 K 0.04 O j .

[0115] Comparative Example 2

[0116] (1) Weigh 1 mol of Mo ammonium heptamolybdate and 0.04 mol of K potassium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.2 mol of Fe ferric nitrate, 0.7 mol of Co cobalt nitrate, 0.2 mol of Ni nickel nitrate and 0.2 mol of Ce cerium nitrate and dissolve them in 200 ml of water to form a second solution. The first solution and the second solution are mixed to obtain a slurry, which is concentrated at 70° C., dried at 100° C. for 12 h, and then calcined at 300° C. for 2 h to obtain a solid precursor.

[0117] (2) Crush the solid precursor and sieve it through 200 mesh. Weigh 0.2 mol of bismuth nitrate and dissolve it in an appropriate amount of 10% nitric acid solution to obtain a third solution. Load the third solution on the crushed solid precursor, add appropriate amount of water and methyl cellulose, cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm, dry at 120°C for 3 hours, and calcine at 400°C for 2 hours to obtain a shaped precursor. Then bake at 90°C for 6 hours and calcine at 550°C for 4 hours to obtain the catalyst Bi 0.2 MoFe 0.2 Co 0.7 Ni 0.2 Ce 0.2 K 0.04 O j .

[0118] Comparative Example 3

[0119] The method of Example 1 is followed, except that water of equal mass is used to replace the nitric acid solution, and the other conditions are the same as those of Example 1; specifically, as follows:

[0120] (1) Weigh 1 mol of Mo ammonium heptamolybdate and 0.04 mol of K potassium hydroxide and dissolve them in 200 ml of water to form a first solution; weigh 0.2 mol of Fe ferric nitrate, 0.7 mol of Co cobalt nitrate, 0.2 mol of Ni nickel nitrate and 0.2 mol of Ce cerium nitrate and dissolve them in 200 ml of water to form a second solution. The first solution and the second solution are mixed to obtain a slurry, which is concentrated at 70° C., dried at 100° C. for 12 h, and then calcined at 300° C. for 2 h to obtain a solid precursor.

[0121] (2) The solid precursor was crushed, sieved through a 200-mesh sieve, and water and methyl cellulose were added to extrude and cut into Raschig rings with an outer diameter of 5 mm, an inner diameter of 3.5 mm, and a length of 4.5 mm. The rings were dried at 120° C. for 3 h, and calcined at 400° C. for 2 h to obtain a molded precursor.

[0122] (3) Weigh 0.2 mol of bismuth nitrate and dissolve it in water to obtain a third solution, impregnate the third solution onto the molded precursor, bake at 90° C. for 6 h, and calcine at 550° C. for 4 h to obtain a catalyst Bi 0.2 / (MoFe 0.2 Co 0.7 Ni 0.2 Ce 0.2 K 0.04 ) j .

[0123] Table 1

[0124]

[0125] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An oxidation catalyst, characterized in that The general formula of the catalyst is: Bi a / (MoFe b X c Y d Z e ) j , wherein X is selected from at least one of Mg, Co, Ni, Ca, Cu, Zn, and Mn; Y is selected from at least one of La and Ce; Z is selected from at least one of K, Rb, Na, and Cs; a is the molar ratio of Bi to Mo, and the value of a is 0.1-0.3; b is the molar ratio of Fe to Mo, and the value of b is 0.1-0.5; c is the molar ratio of X to Mo, and the value of c is 0.5-1.5; d is the molar ratio of Y to Mo, and the value of d is 0.1-0.5; e is the molar ratio of Z to Mo, and the value of e is 0.01-0.06; j is the total number of oxygen atoms required to satisfy the valence of other elements; in the catalyst, the surface dispersion of Bi element is 1-3.

2. The oxidation catalyst according to claim 1, wherein The surface dispersion of Bi element is 1.2-2.8; and / or The value of a is 0.15-0.2; and / or The value of b is 0.15 to 0.3; and / or The value of c is 0.7-1.2; and / or The value of d is 0.15 to 0.3; and / or The value of e is 0.02~0.

05.

3. The oxidation catalyst according to claim 1, wherein X is selected from Co and Ni; and / or Y is selected from La and Ce.

4. A method for preparing an oxidation catalyst, characterized in that: The method includes: (1) dissolving a Mo compound and a Z compound in water to form a first solution; dissolving an Fe compound, an X compound and a Y compound in water to obtain a second solution; mixing the first solution and the second solution to obtain a slurry, and concentrating, drying and calcining to obtain a solid precursor; (2) crushing the solid precursor, molding it with a binder and water, drying it, and calcining it to obtain a molded precursor; (3) dissolving the Bi compound in an acid solution to obtain a third solution, impregnating the third solution onto the molded precursor, drying, and calcining to obtain a catalyst; The amount of each substance fed to the catalyst is such that the general formula is: Bi a / (MoFe b X c Y d Z e ) j , wherein X is selected from at least one of Mg, Co, Ni, Ca, Cu, Zn, and Mn; Y is selected from at least one of La and Ce; Z is selected from at least one of K, Rb, Na, and Cs; a is the molar ratio of Bi to Mo, and the value of a is 0.1 to 0.3; b is the molar ratio of Fe to Mo, and the value of b is 0.1 to 0.5; c is the molar ratio of X to Mo, and the value of c is 0.5 to 1.5; d is the molar ratio of Y to Mo, and the value of d is 0.1 to 0.5; e is the molar ratio of Z to Mo, and the value of e is 0.01 to 0.06; j is the total number of oxygen atoms required to satisfy the valence of other elements.

5. The preparation method according to claim 4, wherein In step (2), The solid precursor is crushed into particles smaller than 100 microns; and / or Drying conditions include: temperature of 100-150°C; and / or time of 1-4h; and / or The calcination conditions include: a temperature of 350-450° C.; and / or a time of 1-3 hours.

6. The preparation method according to claim 4 or 5, wherein: In step (3), In the acid solution, the mass concentration of the acid is 3wt-20wt%; preferably, the acid is selected from nitric acid; and / or The impregnation method is equal volume impregnation; and / or Drying conditions include: temperature of 80-100°C; and / or time of 2-10h; and / or The calcination conditions include: a temperature of 500-600° C.; and / or a time of 1-6 hours.

7. An oxidation catalyst prepared by the preparation method according to any one of claims 4 to 6.

8. Use of the oxidation catalyst according to any one of claims 1 to 3 or the oxidation catalyst according to claim 7 in the oxidation of olefins to prepare olefinic aldehydes and / or olefinic acids.

9. A method for selective oxidation of propylene, characterized in that: The method comprises: contacting a raw material gas containing propylene, an oxidizing gas containing oxygen and a catalyst to prepare acrolein and / or acrylic acid; the catalyst comprises the oxidation catalyst according to any one of claims 1 to 3 or the oxidation catalyst according to claim 7; Preferably, the contact conditions include: The temperature is 300-550°C, preferably 330-380°C; The pressure is 0.01~0.08MPa, where the pressure is gauge pressure; The raw gas volume mass space velocity is 1500-3000 mL / g·h; and / or In terms of volume ratio, propylene: oxygen-containing oxidizing gas = 1: (6-8).

10. The oxidation method according to claim 9, wherein: The raw gas also contains diluent gas phase material; in terms of volume ratio, propylene: diluent gas phase material = 1: (0.5-5); Preferably, the diluent gaseous material is water vapor; and / or The oxygen-containing oxidizing gas is one or more of oxygen and air, more preferably air.

Citation Information

Patent Citations

  • Preparation of acrolein and acrylic acid

    CN1210511A

  • Process for mfg. acrolein and propenoic acid

    CN1283604A

  • Method for acrylic aldehyde and propenoic acid

    CN1314331A

  • Improvement in thrashing-machines

    US141153A

  • Olefin oxidation catalyst and process for its preparation

    US4224187A